POTENSI ARANG AKTIF DARI TULANG KERBAU SEBAGAI ADSORBEN ION BESI, TIMBAL, SULFAT DAN KLORIDA DALAM LARUTAN - Ardha Handayani; Subardi Bali; Itnawita ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Buffalo bone is a waste material that has not been used optimally. One alternative utilization is used as an adsorbent in the form of activated charcoal. Activated charcoal is obtained through the activation process by using Na2CO3 with optimum concentration of 5%. The results of  the  characterization  of  water content, ash content, iodium adsorption and surface area  are  5,66%; 10,21%; 207,48  mg/g  and  5,1058  m2/g respectively.  Activated charcoal adsorption capability is  potentially used for cation adsorption of Fe3+ and Pb2+ by 99,93 and 99,94%, that were analyzed using AAS. Futhermore, adsorption of SO42- ions is 52,93% that was analyzed using a UV-Vis  spectrophotometer. On the other hand, it is  not good enough for Cl- ion uptake that is 10% which was analyzed using methods Argentometry Mohr.